What will I do? Toward an existential ethics for first person action research practice - COGHLAN, DAVID (Rainer HamppVerlag, 2013)
How first person practice engages with the process of valuing has not received much attention in action research. This article takes the question, `what will I do?? as the foundation for first person ethical inquiry. It explores the process of how we are able to experience, to understand and to make value judgements about what is `worthwhile? or `truly good? and so to make choices and to take action. The article marks a move away from a focus on ethics as a set of coherent concepts and definitions to a focus on interiority where ethics are considered in terms of appropriating the activities of valuing, a move from a system based on logic to a system grounded in method, from ethics imposed from outside to personal authenticity.
PUBLISHED
Keywords: action research ethics; first person practice; Bernard Lonergan